A METAPHORICAL THEORY OF MEANING - Clifton Pye (Linguistik Indonesia, 2017)
Languages combine form and meaning in order to express an infinite number of ideas. Modern linguistics has developed sophisticated methods to probe the formal structure of languages from phonetics to syntax, but the study of meaning remains relatively unexplored. The lack of sophisticated methods to document the semantic structure of languages remains a significant problem for work with endangered languages. Research in semantics is limited by semantic theories that can be traced back to Plato and Aristotle. These theories assume that languages use a universal set of semantic elements to construct meaning. The classical theories cannot account for semantic change and an explanation of metaphor is completely beyond the scope of such theories. In this paper I propose a theory of semantics that puts metaphor at the center of semantics. Rather than create an artificial dichotomy between figurative and non-figurative language, the metaphorical approach to semantics assumes that all languages are figurative. This approach assumes that a basic sentence as “The cat is on the mat” combines figurative language with pragmatic information to communicate a basic proposition. This approach differs from that of Lakoff (1993) in that its focus is on metaphoric mapping within cognitive domains rather than between domains. The trick in metaphorical semantics is to learn how to detect the metaphors used in basic linguistic expressions and to construct a theory of semantics based on metaphor.